2022
DOI: 10.3389/fpsyt.2022.943509
|View full text |Cite
|
Sign up to set email alerts
|

Recruiting and exploring vulnerabilities among young people at risk, or in the early stages of serious mental illness (borderline personality disorder and first episode psychosis)

Abstract: IntroductionMany gaps exist in our understanding of the developmental pathways to severe mental illness (SMI), including borderline personality disorder (BPD) and psychosis. However, those who have experienced adverse childhood experiences (ACEs) are at an increased risk and there is evidence to suggest that one of the earliest markers is emotional dysregulation. An area which has received relatively less research attention is the role neurodevelopmental disorders (NDDs) play. The aim of this feasibility study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…7 studies ( Koutsouleris et al, 2014 ; McMillan et al, 2017 ; Sanchez et al, 2019 ; Seiler et al, 2020 ; Burke et al, 2022 ; Gajwani et al, 2022 ; Gruber et al, 2023 ) included patients at CHR-P and patients with BPD, with or without additional samples of patients with FEP or major depressive disorder/mood disorders and healthy controls. In this theme, CHR-P and BPD represented different clinical populations (even though some CHR-P youth also displayed a comorbid BPD).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7 studies ( Koutsouleris et al, 2014 ; McMillan et al, 2017 ; Sanchez et al, 2019 ; Seiler et al, 2020 ; Burke et al, 2022 ; Gajwani et al, 2022 ; Gruber et al, 2023 ) included patients at CHR-P and patients with BPD, with or without additional samples of patients with FEP or major depressive disorder/mood disorders and healthy controls. In this theme, CHR-P and BPD represented different clinical populations (even though some CHR-P youth also displayed a comorbid BPD).…”
Section: Resultsmentioning
confidence: 99%
“…Clinical recommendations included assessing sub-threshold positive symptoms in help-seeking youth even though their major complaint is non-psychotic ( Seiler et al, 2020 ), screening for neurodevelopmental disorders and adverse childhood experiences ( Gajwani et al, 2022 ), integrating sexual health screening into initial assessment ( Sanchez et al, 2019 ), and implementing a range of strategies to address sexual health and sexual dysfunction ( McMillan et al, 2017 ). Gruber et al emphasized the clinical implications of comprehensive assessment measures to evaluate identity- and self-disturbances ( Gruber et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Juurlink et al (2021) found that identity instability and chronic emptiness predicted vocational di culties, while perceived social support has been shown to act as a protective factor against functional impairment (Thadani et al, 2022). As such, it is important to be open to all forms of trials and interventions for BPD in adolescents and young adults as the work is still in its nascent stages in clinical and community settings(Gajwani et al, 2022). The awaited ODDESSI trial, an RCT exploring Open Dialogue Therapy's effects, a social network model of crisis and continuing mental healthcare, could offer valuable insights into the impact on functioning and recovery(Pilling et al, 2022).Findings indicated a slight increase in ES at the nal follow-up for longer-term outcomes in specialist BPD interventions.…”
mentioning
confidence: 99%